Valuasi Ekonomi Ekosistem Hutan Mangrove di Desa Betahwalang, Kecamatan Bonang, Kabupaten Demak, Jawa Tengah - Bellatris Santri; Rudhi Pribadi; Irwani irwani (Journal of Marine Research, 2020)
ABSTRAK: Ekosistem hutan mangrove memiliki 3 fungsi utama yaitu fungsi fisik, fungsi ekologis dan fungsi ekonomi. Pemanfaatan ekosistem mangrove semakin meningkat sehingga menyebabkan kerusakan dan penurunan jasa lingkungan. Untuk menghindari hilangnya fungsi ekosistem hutan mangrove maka perlu dilakukan konservasi mangrove dengan upaya rehabilitasi. Perhitungan valuasi ekonomi untuk mengetahui kerugian dari hilangnya nilai ekonomi ekosistem hutan mangrove. Tujuan dari penelitian ini adalah mengetahui nilai guna (use value) maupun nilai non guna (non use value) dan nilai ekonomi total ekosistem hutan mangrove di Desa Betahwalang, Kecamatan Bonang, Kabupaten Demak. Metode yang digunakan dalam penelitian ini adalah metode deskriptif eksploratif yang ditekankan pada kuantifikasi total nilai pemanfaatan langsung maupun tidak langsung ekosistem hutan mangrove. Sampel penelitian yang diambil adalah masyarakat yang mempunyai mata pencaharian berkaitan dengan keberadaan ekosistem hutan mangrove secara langsung dan tidak langsung. Hasil penelitian menunjukkan nilai ekonomi total ekosistem hutan mangrove di Desa Betahwalang adalah sebesar Rp 1.510.046.534/tahun yang didapatkan dari nilai guna (use value) sebesar Rp 817.443.034,35/tahun dan nilai non guna (non use value) sebesar Rp 692.603.500/tahun.  ABSTRACT: The mangrove forest ecosystem is an ecosystem located along the coast or river estuary that is influenced by the tide of sea water. The existence of this ecosystem has a very important role in the surrounding environment, either directly or undirectly. The Mangrove forest ecosystem has 3 main functions, physical, ecological and economic function. The utilization of mangrove ecosystem by the community is increasing and causing damage to the mangrove forest ecosystem. To avoid the loss of ecosystem function of mangrove forest, it needs to be renewed with mangrove rehabilitation. Calculation of economic valuation to determine the loss of economic value of the mangrove forest ecosystem if its existence is not maintained properly. This research has purposes for knowing the use value or non use value and the total economic value of the mangrove forest ecosystem in Betahwalang Village, Bonang District, Demak Regency. The methods used in this research are descriptive and explorative method that is emphasized on quantifying the total value of direct or undirect utilization of mangrove forest ecosystems. The method of discourse is used to describe the socio-economic activities of the community and the condition of mangrove forest ecosystem through interviews. Exploratory method is a method to find out the problems that exist in the community and natural phenomena that can affect the existence of economic value of the mangrove forest ecosystem. The results showed the total economic value of the mangrove forest ecosystem in the Betahwalang village is Rp. 1.510.046.534/year consisting of use value of Rp. 817.443.034.35/year and non use value Rp 692.603.500/year. The use value includes direct use value Rp 800.275.000/year and option value Rp 17.168.034.35/year. The non use value include existence value Rp 612.576.000/year and bequest value Rp 80.027.500/year.